THE UTILIZATION OF EU FUNDS IN THE YEARS 2007–2015 FOR THE PRESERVATION OF CULTURAL HERITAGE OF RURAL AREAS IN EASTERN POLAND - Gralak, Arkadiusz; Powęska, Halina (Acta Scientiarum Polonorum. Oeconomia, 2017)
The article presents the problems of financing cultural heritage of rural areas from the European Union funds in the macroregion of Eastern Poland. It outlines the scale and structure of the use of the EU funds for projects relating to the protection and promotion of cultural heritage. It also describes the scale of regional differentiation in the field of the use of European Funds for the protection of cultural heritage in rural areas. The temporal range of the study included the years from 2007 to 2015. The analysis was conducted across the six types of projects distinguished according to their subject matter, that is to say the promotion of natural values, protection and valorization of natural heritage, other forms of support for the enhancement of tourism services, protection and preservation of cultural heritage, development of cultural infrastructure, other forms of support for the improvement of cultural services, as well as integrated projects for the revitalization of urban and rural areas. The analysis focused on four types of areas: rural areas, towns with county rights, voivodship towns and the area of the voivodship. The information used in this study was based on the data pertaining to the projects co-financed from the EU funds and stored in the National Information System (KSI SIMIK 07-13) as of 31 December 2016.